PKM Peningkatan Produksi Kerajinan Bambu dalam Memperbaiki Pendapatan Kelompok Pengrajin Bambu Di Kelurahan Kinilow Kecamatan Tomohon Utara Kota Tomohon - Zuldesmi Zuldesmi; Robert R. Winerungan; Moh. Fachruddin Suharto (PENGABDI, 2020)
The production process of woven bamboo which starting from the cutting down, the skinning, the breaking until the depleting processes is still traditional or manual by using machete and knife. Therefore, the product performance has a low quality because there is un-uniform in a product size (especially in the thickness) and form. This process also has been doing by the small  bamboo entrepreneurs in a city that has many people craft’s industries and one of them is a bamboo craft industry, Tomohon city. In order to solve that problem, in this activity, we applied a bamboo splitting machine which can increase the quantity and quality of bamboo parts production for bamboo crafts. Bamboo splitting machine is a machine that works to split or devide bamboo with the widht of bamboo that can be arranged as needed. This machine is used to help produce bamboo part products in large quantities by saving time and labor. The results show that this bamboo splitting machine has an average capacity of 5000-6000 parts / hour (about six times higher than which manual process). So that the productivity and quality of products made of bamboo can be improved and uniform according to consumer standards. Besides, tiredness and pains of workers can be released by using a bamboo depletion machine